Biocompatibility improvement and controlled in vitro degradation of poly (lactic acid)‐b‐poly(lactide‐co‐caprolactone) by formation of highly oriented structure for orthopedic application. Issue 11 (8th June 2022) - Wang, Wuyou; Liu, Yalong; Ye, Lin; Coates, Phil; Caton‐Rose, Fin; Zhao, Xiaowen
Abstract: Poly (lactic acid) (PLA) has been proposed as a promising orthopedic implant material, whereas insufficient mechanical strength, unsatisfied biocompatibility and inappropriate degradation rate restrict its further application. In this work, self‐reinforced poly (lactic acid)‐ b ‐poly(lactide‐ co ‐caprolactone) (PLA‐ b ‐PLCL) block copolymer with long‐chain branches was fabricated through two‐stage orientation. Compared with smooth and hydrophobic PLA surface, the surface of PLA‐b‐PLCL presented micro‐phase separated structure with improved hydrophilicity, and cells seeded on it showed improved adhesion/proliferation and high alkaline phosphatase (ALP) activity. After the 1st stage orientation at temperature higher than Tg1 (glass transition temperature of PLA phase), the amount of CH3 and CO groups on surface of PLA‐b‐PLCL increased, while "groove‐ridge" structure formed, resulting in enhancement of surface hydrophobicity. After the 2nd stage orientation at Tg1  ~ Tg2 (glass transition temperature of PLCL phase), surface hydrophobicity/amount of CO groups further increased and "groove‐ridge" structure became more significant. Due to suitable wettability and enhanced material‐cell mechanical interlocking, cell proliferation/ALP activity were improved and a continuous cell layer formed on sample surface. During in vitro degradation in phosphate buffered saline solution, by introduction of PLCL segments, the crystallinity decreased and solution absorption increased, resulting in a rapid deterioration of mechanical properties. After the 1st stage orientation, a dense microfibrillar structure with high crystallinity formed, which hindered diffusion of solution and delay hydrolytic degradation. After the 2nd stage orientation, PLCL segments were arranged more closely, resulting in a further inhibition of degradation, which was helpful for controlling the strength decay rate of PLA as bone fixation materials. Abstract :